DAMPAK COVID 19 DAN STRATEGI KELOMPOK SADAR WISATA (POKDARWIS) DALAM MENGELOLA DESA WISATA DI KABUPATEN PAMEKASAN - Ratna Azis Prasetyo; Karnaji; Sutinah; Udji Asiyah (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
The Pamekasan Regency Government's policy on thematic villages has been responded to by the community with the development of tourist villages. This is not without reason considering the many tourism potentials and tourism products in Pamekasan Regency. Each establishment of a tourist village is managed by Pokdarwis in the village. In this postmodern era, tourist villages are very popular in Indonesia because some of them not only offer tourist designs such as tours abroad, but in the midst of tourist boredom with artificial designs, many tourists also want tours with a back to nature theme. Pamekasan Regency has both tourism design potentials because this area has a coastline as well as hills, some of which are designed to resemble tourist objects abroad, some of which are naturally designed. The growth of tourism in Pamekasan has a positive impact on people's economic growth. However, since the COVID-19 pandemic, income from the tourism sector has decreased or even not existed at all due to a number of policies to control the transmission of the Covid 19 virus. This study used a qualitative method with data collection through FGD (Focus Group Discussion) to 12 informant Pokdarwis representatives in Pamekasan Regency. The results of this study found that Pokdarwis and tourism actors who had depended on the tourism sector were the most disadvantaged groups due to the covid 19 pandemic. On the other hand, they must still be able to manage tourism places so they don't close forever or collapse. Some of the strategies they have implemented include continuing to open tourism places with restrictions on the number of visitors, promoting in digital media, and enforcing a ticket reservation system for visitors.